KEMULURAN DAN KEKUATAN PUTUS TALI SABUT KELAPA BERLAPIS KITOSAN: Elongation and Breaking Strength of The Chitosan-Coated Coir Rope - Didin Komarudin; Diniah Diniah; M. Dahri Iskandar; Dwi Putra Yuwandana; Yopi Novita (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
Coating of coconut coir rope as a material for fishing gear is carried out to inhibit the decomposition process and increase the breaking strength and elongation of the rope. In this study,the coating of coconut coir rope using chitosan as an antimicrobial is expected to inhibit the growth of micro-organisms. This study aims to determine the elongation and breaking strength of chitosancoated coconut coir ropes. The research method used is experimental. Data analysis used the Kolmogorov–Smirnov normality test and RAL (Completely Randomized Design)- to determine the effect of chitosan coating on the elongation and breaking strength of coconut fiber ropes. The results showed that the chitosan coir rope had a dark brown color, while the control coir rope had a light brown color. The direction of the twist is "S", with a "hard" type of twist so that the rope tends to be stiff. The fiber type is staple fiber (short fiber). The elongation of the chitosan coir rope was 10.21 cm, 17.55% higher than the untreated coconut coir rope, which was 8.68 cm. The average breaking strength of chitosan coir rope was 37.41 kgf or 11.87% higher than untreated coconut coir rope, which was 33.44 kgf. Keywords: elongation, breaking strength, chitosan, chitosan coconut fiber rope.